Work-life balance as a mediator between flexible work arrangements and job performance among women in the banking industry - Tan, Yu Xian; Seow, Ai Na; Lam, Siew Yong (International Journal of Accounting, Finance and Business, 2025)
The rising demands of work expectations, combined with the challenges of maintaining work-life balance among female employees, have further emphasised the necessity of flexible work arrangements in the banking industry. This study examines the relationship between flexible work arrangements, work-life balance, and job performance among female banking employees in Malaysia. The Social Exchange Theory was used to explore these relationships. A total of 385 completed questionnaires were collected through an online survey. The partial least squares are employed for a comprehensive structural equation modelling analysis. The results indicated that flexible work arrangements are positively related to job performance, directly and indirectly, through improved work-life balance. The study contributes to the existing literature by highlighting the mediating role of work-life balance and providing practical insights for banking institutions and policymakers. By implementing flexible work arrangements in the working environment, banking institutions can create a supportive culture that improves work-life balance and increases job performance further.